Penerapan Manajemen Risiko terhadap Perwujudan Good Corporate Governance pada Perusahaan Asuransi - Yana Ayu Pradana; Brady Rikumahu (Faculty of Economics and Business, University of Pasundan, 2014)
Good Corporate Governance (GCG) is a system used to direct and control the company’s business activities. Risk emerges with the business activities of the company to achieve the company’s strategic objectives. Company needs to manage these risks to minimize the impact of risk and achieve the company’s strategic objectives. This study focuses on the effects that arise from the application of risk management to the realization of GCG through principles of GCG. There are 15 respondents from one of the State-Owned Enterprises in the area of insurance. Research shows that a significant difference between risk management and corporate governance of 53.40%. Risk management has an important role in the realization of corporate governance through effective risk management, so that the company can minimize the risks and impacts more carefully to take opportunities.